Maltodextrin from Sweet Cassava: A Promising Endurance Enhancer - Kakanang Posridee; Anant Oonsivilai; Ratchadaporn Oonsivilai (Foods, 2024)
The effects of maltodextrin and crude extract from sweet cassava on exercise endurance were examined in the male Wistar rat. The rats were randomly assigned to either an exercise training group or a non-exercise training group. Both groups were further divided into subgroups that received either a control, crude extract (250 or 500 mg/kg), or maltodextrin (250 or 500 mg/kg) orally once daily for 16 days. The time to the point of exhaustion after weight-loaded forced swimming was measured on day 16. Body weight gain, relative organ weight, biochemical parameters, and liver and gastrocnemius muscle glycogen content were also determined. Maltodextrin at a dose of 500 mg/kg significantly increased the time to the point of exhaustion compared to all other groups. Maltodextrin and crude extract with both doses significantly increased liver and gastrocnemius muscle glycogen content compared to the control group. There were no significant differences in glucose, BUN, triglyceride, or insulin levels between the groups. Crude extract at a dose of 250 mg/kg significantly increased AST and ALT levels, and LDH levels significantly increased in the exercise training group. Creatinine levels were significantly higher in the exercise training group compared to the non-exercise training group. Exercise boosted antioxidant enzymes, glycogen, and reduced damaging free radicals in the rats. Maltodextrin and crude extract further amplified this effect by activating AMPK and PGC-1α, suggesting that they combat fatigue through an antioxidant pathway linked to AMPK. These findings suggest that maltodextrin and crude extract from sweet cassava may have the potential to enhance exercise endurance. They may increase glycogen storage in the liver and gastrocnemius muscle, potentially through improved glycogen reserves and glycogen sparing effects. Further studies are needed to elucidate the mechanisms underlying these effects.